2007
DOI: 10.1002/jor.20503
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the bone mineral density in proximal femur following total hip resurfacing arthroplasty in osteonecrosis of femoral head

Abstract: Total hip resurfacing arthroplasty (THRA) is being performed with increasing frequency for osteonecrosis of femoral head (ONFH). To evaluate femoral bone remodeling in ONFH after THRA and determine the impact of stem-neck angle (SNA) of inserted femoral component on bone remodeling, we monitored the changes in BMD in proximal femur in 23 patients with ONFH after surgery. Patients were divided into group A (SNA ! 58) and group B (SNA < 58). The BMD was measured in seven Gruen zones and two neck zones using dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
(49 reference statements)
0
23
1
Order By: Relevance
“…All these changes are characteristic of most comparable hip resurfacing femoral components (Amstutz, Beaulé et al 2004;Spencer et al 2008), and were under-predicted by the model if the established control algorithm was used with the literature standard 75% threshold remodelling stimulus. More extensive resorption was predicted if a smaller threshold remodelling stimulus of 62.5% was used, but this is in disagreement with quantitative clinical data which shows a clear loss-recovery trend in the lateral neck and a progressive BMD increase in the medial neck (Lian et al 2008), especially distal to the head-neck junction (Kishida et al 2004;Häkkinen et al 2011;Penny et al 2012;Gerhardt et al 2014). Quantitative comparison of the predicted and clinically measured BMD changes remains difficult with hip resurfacing implants, owing to the variety of DXA zone definitions in these cited studies.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…All these changes are characteristic of most comparable hip resurfacing femoral components (Amstutz, Beaulé et al 2004;Spencer et al 2008), and were under-predicted by the model if the established control algorithm was used with the literature standard 75% threshold remodelling stimulus. More extensive resorption was predicted if a smaller threshold remodelling stimulus of 62.5% was used, but this is in disagreement with quantitative clinical data which shows a clear loss-recovery trend in the lateral neck and a progressive BMD increase in the medial neck (Lian et al 2008), especially distal to the head-neck junction (Kishida et al 2004;Häkkinen et al 2011;Penny et al 2012;Gerhardt et al 2014). Quantitative comparison of the predicted and clinically measured BMD changes remains difficult with hip resurfacing implants, owing to the variety of DXA zone definitions in these cited studies.…”
Section: Discussioncontrasting
confidence: 57%
“…For some time there was limited quantitative clinical evidence of periprosthetic BMD changes (Cohen and Rushton 1995;Wilkinson et al 2001), and only more recently has the availability of DXA data become sufficient to enable more thorough spatiotemporal assessment of the validity of these predictions across the full periprosthetic region: for cemented THR (Jayasuriya et al 2013), cementless THR (Leichtle et al 2005;Kim et al 2007;Penny et al 2012), and for hip resurfacing (Kishida et al 2004;Lian et al 2008;Häkkinen et al 2011;Penny et al 2012;Huang et al 2013;Gerhardt et al 2014). This data demonstrated that past modelling studies have not reproduced clinically representative temporal trends of remodelling.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some of these patients also developed neck narrowing and, in a recent cohort of 377 patients, Little et al [8] reported that 4% of the patients had undergone femoral neck fracture. Although there is a growing body of evidence that the bone mineral density (BMD) is decreased around the implant in the first postoperative months, this could be attributed to the operation itself, as BMD seemed to increase after 3 months post-surgery [9][10][11]. Recent reports suggest that, besides bone density, other factors, often referred as ''bone quality", influence bone strength.…”
Section: Introductionmentioning
confidence: 92%
“…The whole femoral neck (R1) was analysed as one region and calculations were made. Several finiteelement analyses and original articles of case series in the literature reveal that bone remodelling is not uniform across the entire femoral neck [2][3][4]. The superolateral area adjacent to the implant has evinced a relative stress shielding [2].…”
mentioning
confidence: 99%